Pengaruh Promosi dan Efektivitas Kampanye Influencer Marketing dalam Meningkatkan Kesadaran Merek Produk Kecantikan “Esqa” di Indonesia - Tiara Aulia Al Aziz (VISA: Journal of Vision and Ideas, 2024)
Influencer marketing is the most important new marketing approach of the last decade for professionals on the front lines of purchasing decisions. According to Grenny (2014) said that the ability to make changes in someone's behavior and the person who does it is an influencer or influencer. This research uses a quantitative type of research. The approach used in this research is a survey approach, namely research that takes samples from the population and uses questionnaires as the main data collection tool. This research was conducted to explain the influence of promotion and effectiveness of influencer marketing campaigns on brand awareness. Based on the test results, it was found that Promotion (X1) individually had a significant effect on Brand Awareness (Y) of ESQA Cosmetics, as shown by the calculated t value of 3.138 which exceeded the t table of 1.660. Likewise, Influencer Marketing Campaign Effectiveness (X2) also has a significant impact on Brand Awareness (Y), with a calculated t value of 4.261 which is higher than the t table of 1.660. Furthermore, in a simultaneous test, both Promotion (X1) and Influencer Marketing Campaign Effectiveness (X2) together have a significant effect on Brand Awareness (Y) of ESQA Cosmetics, as shown by the calculated F value of 12.424 which exceeds the F table value of 3.09. Therefore, it can be concluded that there is a significant influence between Promotion (X1) and Influencer Marketing Campaign Effectiveness (X2) simultaneously on Brand Awareness (Y) of ESQA Cosmetics.